The state of statelessness: justice, violence, subjectivity, and urban asylum seeking and refugee women in Cairo - Wahba, Mariham Iskander (AUC Knowledge Fountain, 2010)
Cairo is a complex urban city and this is the landscape upon which various struggles occur. In 1997 UNHCR released their â Comprehensive Policy on Urban Refugeesâ in response to the increasing numbers of refugees in urban areas. UNHCR acts as the ultimate â space allocaterâ and examines who â deservesâ to access urban space and who is or is not and â urbanâ refugee. Justice in this case becomes a highly spatialized concept and as a consequence, accessing justice also becomes a spatialized process. For asylum seeking and refugee women in Cairo, justice and access to this commodity is not only spatialized, but also gendered. Conceptions of justice, particularly that which is conceptualized via the medium of human rights, were initially conceptualized as pertaining fundamentally to a male subject. This raises significant concerns regarding the gendered nature of the definition of, distribution of, and access to rights. The space that was created within these structures for women as a consequence of advocacy in the late 80's and 90's was a space that signified the importance of physical over structural violence and sexual crimes over crimes of a different nature. A consequence of the political project of creating this space for women's rights in this particular manner was that women's voices were silenced if they did not follow the dominant narrative expected and their subjectivities were constructed and manipulated for political means. Women in this context became constituted through law as â vulnerable bodiesâ and â sexualized victimsâ . Through various processes such as advocacy, refugee status determination, and service provision, refugee women's subjectivities are constructed and imposed by UNHCR, the international community, and by refugee advocates. The embodiment of this construction and its institutionalization as well as portrayal comes out in many narratives concerning urban refugee women and sexual and gender based violence in Cairo. The specific categories that UNHCR sets up such as â women at riskâ or other fast track procedures, creates a situation whereby sexualized victimhood becomes a commodity. Women must perform this sexual vulnerability in ways that are scripted and stereotyped to be perceived as â credibleâ . If not, they are deemed as incredible and lose access to services as well as the much sought after title of refugee.